Obesity and its implications on nononcological urological surgery. Issue 5 (September 2017) - Mari, Andrea; Abufaraj, Mohammad; Mansy, Karim; Sievert, Karl-Dietrich
Abstract : Purpose of review: To review and summarize the current literature of the implications of obesity on nononcological urological surgery. We conducted a comprehensive search of the current literature with emphasis on the published literature in the last 18 months. Recent findings: Over time, obese patients have become a more common encounter in clinical practice. Obesity represents a considerable operative challenge and has been linked to a higher rate of postoperative complications. Data regarding surgery for incontinence are inconsistent. Nevertheless, the success rates in obese women are high, and complication rates are relatively low with comparable results to nonobese women. In renal surgery, percutaneous nephrolithotomy and minipercutaneous nephrolithotomy are feasible, well tolerated, and effective even in obese patients. However, certain precautions and availability of proper instruments are necessary. Summary: Although randomized clinical data are lacking and the results of many studies are inconsistent, evidence supports the feasibility and safety of different nononcological urological interventions in obese patients. Moreover, the success rates and the overall complication rates seem to be comparable to nonobese patients with some exceptions.